Dynamical System of a Mosquito Population with Distinct Birth-Death Rates - Boxonov, Z.S.; Rozikov, U.A. (Journal of Applied Nonlinear Dynamics, 2026)
We study the discrete-time dynamical systems of a model of wild mosquito population with distinct birth (denoted by $β$) and death (denoted by $μ$) rates. The case $β=μ$ was considered in our previous work. In this paper we prove that for $βμ$ the population will survive, namely, the number of the larvaes goes to infinite and the number of adults has finite limit ${α\over μ}$, where $α>0$ is the maximum emergence rete.